2002
DOI: 10.1046/j.1328-8067.2001.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Mizoribine treatment for childhood IgA nephropathy

Abstract: Mizoribine can be an alternative drug for childhood IgAN with moderate severity because it results in a significant reduction of proteinuria and hematuria with histological improvement and causes far fewer complications compared to the conventional immunosuppressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Currently, MZR is used for the treatment of renal diseases including IgA nephropathy, nephrotic syndrome, lupus nephritis, and purpura nephritis, and is safe, reliable, and with acceptable efficacy. [8][9][10][11][12][13][14][15][16][17] As MZR increases the transcription activities of glucocorticoid receptors, 5,18 increases the efficacy of glucocorticoids, and reduce, the viral replication induced by long-term use of high-dose glucocorticoids, the present study investigated the efficacy of MZR in combination with moderate dose of glucocorticoids in treating patients with HBV-positive nephrotic syndrome. In the present clinical study, methylprednisolone, MZR, and entecavir were used as the combination treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, MZR is used for the treatment of renal diseases including IgA nephropathy, nephrotic syndrome, lupus nephritis, and purpura nephritis, and is safe, reliable, and with acceptable efficacy. [8][9][10][11][12][13][14][15][16][17] As MZR increases the transcription activities of glucocorticoid receptors, 5,18 increases the efficacy of glucocorticoids, and reduce, the viral replication induced by long-term use of high-dose glucocorticoids, the present study investigated the efficacy of MZR in combination with moderate dose of glucocorticoids in treating patients with HBV-positive nephrotic syndrome. In the present clinical study, methylprednisolone, MZR, and entecavir were used as the combination treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on the treatment of patients having diffuse IgAN with the above-mentioned risk factors in childhood [5, 6, 10, 18, 19,21,22,23]. Welch et al [22] showed no efficacy of prednisone against IgAN in a double-blind, controlled trial of short-term prednisone therapy.…”
Section: Discussionmentioning
confidence: 99%
“…MZB was first approved as a drug to prevent rejection of renal transplants in 1984, and the indications were extended to ‘lupus nephritis’ in 1990 and to ‘primary nephritic syndrome’ in 1995 [28]. Nagaoka et al [19] found that MZB could be used as an alternative drug for treatment of moderate childhood IgAN, because it resulted in a significant reduction of proteinuria and hematuria with histological improvement and caused far fewer complications as compared with conventional immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1(A)] is an effective immunosuppressant isolated from the soil fungus Eupenicillium brefeldianum (Hamasaki et al, 1997;Mizuno et al, 1974;Nagaoka et al, 2002). Its immunosuppressive activity appears to be mediated by the selective inhibition of guanosine monophosphate synthetase and inosine monophosphate dehydrogenase, suppressing nucleic acid synthesis (Koyama and Tsuji, 1983;Kusumi et al, 1989).…”
Section: Introductionmentioning
confidence: 98%